Compras y contrataciones de menor cuantía en la Municipalidad Distrital de San Juan Bautista en el 1er semestre 2023 - Valles Chanchari, Liz Jany (2025)
Smaller purchases and contracting in municipalities generate a great economic movement for our labor and social development, among others, the purpose being to make proper use of the resources available. This thesis seeks to identify the impact that minor purchases and contracting will have in the District Municipality of San Juan Bautista in the 1st semester of 2023. With this objective, this thesis of Quantitative type, Correlational type, Non Experimental design was developed. The research work reaches the conclusion that minor purchases and contracting significantly impacts the District Municipality of San Juan Bautista in the 1st semester of 2023, confirming in the result of the Correlation Coefficient that it was r = 0.775553092. After that, it was shown that small purchases and contracting are mostly used to quickly cover the needs of the municipality and the population as a whole. On the other hand, the analysis of minor purchases and contracting in the municipalities of Peru shows that applying this procedure to acquire goods and/or services.